Tooth discoloration caused by endodontic cements: a literature review (Research, Society and Development, 2022)
Objective: The objective of this work was to identify which is the main endodontic cement that promotes tooth discoloration, in addition to showing which other paths can be followed to avoid aesthetic damage to the treated tooth. Methodology: A search was carried out in English for articles through the PubMed, MedLine, Cochrane and Lilacs databases, from 2005 to 2020. Results: It was observed that most of the tested cement promoted color changes, especially materials based on zinc oxide-eugenol and mineral trioxide aggregate, when applied to anterior teeth, due to the thin structure of this tooth. This is because-of the chemical components present in these materials. The bioceramic components are the ones that promote fewer alterations when compared to the other materials mentioned in this study. Final Considerations: Proper cleaning of the pulp chamber is essential to avoid tooth discoloration after endodontic treatment. Internal tooth whitening and the use of dentin adhesive agents may be alternatives to improve esthetics due to tooth darkening caused by endodontic obturators.